Assessment of bone remodeling in patients with type 2 diabetes mellitus - Sain Sattar Safarova (Zaporožskij Medicinskij Žurnal)
Despite higher femoral neck and lumbar spine bone mineral density (BMD), individuals with type 2 diabetes mellitus (DM2) have 1,5-2 times increased fracture risk than in a healthy population. These data suggest that some indicators may be more informative regarding the prediction of low-trauma fractures risk, which observed in patients with diabetes mellitus, and BMD measurement does not reflect in essence the real trend towards the development of bone remodeling disorders in these patients.